Superman - Bruce, Timm; Duane, Capizzi; Lauren, Montgomery; Brandon, Vietti (Warner Home Video ; distributed in the Philippines by Warner Home Video (Phils.), 2007)
When Lexcorp accidentally unearths the intergalactic serial killer Doomsday, Superman must battle the creature head-on in the fight of his life. The world collectively mourns their fallen hero and humanity realizes it will never feel truly safe again. Superman's enemies rejoice, all but Lex Luthor, who grieves the loss in his own demented manner, setting off a chilling chain of events that even he couldn't have foreseen.